WALISONGO DAN WAYANG (Sebuah Refleksi Sarana Perkembangan Islam di Jawa) - Heru Syahputra (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2019)
The nine Wali’s are believed to be very firm by the Javanese as the first stone foundation of Islam in Java. One of the nine guardians is Sunan Kalijaga. Sunan Kalijaga was very attached to the hearts of the Muslims in Java, more than anything else. The main advantage of it is its ability to incorporate the influence of Islam on the habits of Javanese people. The love of the Javanese who cannot be separated from the puppets caused him to include Islamic saga in wayang games.